A Review on the Study of Strength Properties of High Performance Concrete Using Various Fibers - S, Venkateshwaran; A, Alex Rajesh (International Research Journal of Multidisciplinary Technovation, 2019)
This is review report on High performance Concrete and is done by studying various journal papers on High performance concrete and this paper mainly concentrated on how to improve the Strength of concrete by using various fibers. Fibers are generally used in concrete to improve the tensile strength of the concrete. In fiber Reinforced Concrete (FRC) various types of fibers can be used such as polypropylene, cellulose, carbon, jute, PET fibers and Steel fibers. Among the above all steel fibers shows best performance comparing to other fibers. The flexural strength and compressive strength test are commonly done for every fiber and their values and comparisons are discussed in this report.